Localization of rotavirus VP4 neutralization epitopes involved in antibody-induced conformational changes of virus structure. - Zhou, Y J (1994)
We previously characterized three neutralization-positive epitopes (NP1 [1a and 1b], NP2, and NP3) and three neutralization-negative epitopes on the simian rotavirus SA11 VP4 with 13 monoclonal antibodies (MAbs). Conformational changes occurred as a result of the binding of NP1 MAbs to the SA11 spike VP4, and enhanced binding of all neutralization-negative MAbs was observed when NP1 MAbs bound VP4 in a competitive MAb capture enzyme-linked immunosorbent assay. To further understand the structure and function of VP4, we have continued studies with these MAbs. Electron microscopic and sucrose gradient analyses of SA11-MAb complexes showed that triple-layered viral particles disassembled following treatment with NP1b MAbs 10G6 and 7G6 but not following treatment with NP1a MAb 9F6, NP2 MAb 2G4, and NP3 MAb 23. Virus infectivity was reduced approximately 3 to 5 logs by the NP1b MAbs. These results suggest that NP1b MAb neutralization occurs by a novel mechanism. We selected four neutralization escape mutants of SA11 with these VP4 MAbs and characterized them by using plaque reduction neutralization assays, hemagglutination inhibition assays, and an antigen capture enzyme-linked immunosorbent assay. These analyses support the previous assignment of the NP1a, NP1b, NP2, and NP3 MAbs into separate epitopes and confirmed that the viruses were truly neutralization escape mutants. Nucleotide sequence analyses found 1 amino acid (aa) substitution in VP8* of VP4 at (i) aa 136 for NP1a MAb mutant 9F6R, (ii) aa 180 and 183 for NP1b MAb mutants 7G6R and 10G6R, respectively, and (iii) aa 194 for NP3 MAb mutant 23R. The NP1b MAb mutants showed an unexpected enhanced binding with heterologous nonneutralization MAb to VP7 compared with parental SA11 and the other mutants. Taken together, these results suggest that the NP1b epitope is a critical site for VP4 and VP7 interactions and for virus stability.